2019
DOI: 10.1111/inm.12586
|View full text |Cite
|
Sign up to set email alerts
|

An international survey of Psychiatric‐Mental‐Health Nurses on the content validity of the International Classification of Functioning, Disability and Health Core Sets for Schizophrenia

Abstract: The International Classification of Functioning, Disability and Health (ICF) Core Sets for schizophrenia describe the key problems in functioning that are experienced by individuals with this disorder. This study examines the content validity of these Core Sets and aims to identify the most frequent problems faced by people with schizophrenia, considering for this analysis the perspective of Psychiatric-Mental-Health Nurses. The study complied with the COREQ checklist for qualitative studies. A total of 101 nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Likewise, regardless of the perspective considered, it has been reported that there are certain sections of the ICF in which hardly any categories have been included, as is the case of body structures (Nuño et al, 2019). This can be attributed to the fact that we are facing a mental illness, with a predominance of behavioral disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, regardless of the perspective considered, it has been reported that there are certain sections of the ICF in which hardly any categories have been included, as is the case of body structures (Nuño et al, 2019). This can be attributed to the fact that we are facing a mental illness, with a predominance of behavioral disorders.…”
Section: Discussionmentioning
confidence: 99%
“…This is because previous research on the content validity of the ICF-CS with different professionals (nurses, occupational therapists, physiotherapists, psychiatrists, psychologists, and social workers) has shown that the difference in perspective between health professionals means that some ICF-CS categories for schizophrenia may be more relevant than others for a given health professional, although the way of assessing functionality is the same. [ 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The six Delphi studies were conducted between 2016 and 2018. All studies followed the same design to ensure a high level of comparability between the results of each, and it has been detailed in the previous studies which describe the results obtained from each perspective: psychiatry [27], psychology [28], nursing [29], occupational therapy [30], social work [31] and physiotherapy [32]. Anonymity was guaranteed as the process was coordinated by a research team using an online platform or email, thus avoiding any interaction between the participants.…”
Section: Methodsmentioning
confidence: 99%